Hydrological characteristics and primary production in fish ponds manured with different organic manures - Singh, V K; Sharma, A P (Indian Journal of Fisheries, 2011)
The present study describes the effect of three organic manures viz. cowdung,pigdung and poultry excreta on various hydrobiological parameters and grossprimary productivity in ponds stocked with Labeo rohita. Poultry excretashowed higher values of dissolved oxygen, pH, carbonate and bicarbonatealkalinity and gross primary productivity while cowdung recorded highervalues of free carbondioxide than the other two manured ponds. Thehydrological characteristics and gross primary productivity profiles of pondsreveal that the poultry excreta had better manurial value followed by pigdungand cowdung